Humanistic Approach in Teaching Foreign Language (from the Teacher Perspective) - Arifi, Qatip (European Scientific Journal, ESJ, 2017)
In education, attention was paid almost exclusively to the acquisition of new knowledge and developing work habits of students. As much as the two areas are important, insisting only on them does not develop the skills that students will need later in life, nor will they develop positive attitudes and empathy. Forming socially acceptable attitudes and developing empathy is extremely important if one of the goals of education is to enable students to become responsible members of society. Unlike the traditional approach to education, a humanistic approach emphasizes the importance of the inner world of students; their thoughts, feelings and emotions are put into the forefront of development. This paper deals with the teaching of foreign languages and argues that the humanistic approach in teaching gives better results. The results of a qualitative participatory research dealing with the attitudes of teachers are presented in order to determine the extent to which teachers have awareness of the importance of applying a humanistic approach, and how much the incentive of teachers in the work influences the quality of interaction in teacher-learner and student-student approach. The results of the research indicate that the use of humanistic teaching approaches helps to develop emotionally positive attitudes in students, influences the creation of good relationships in the group, and encourages students to develop language competence.